2010
DOI: 10.1152/jn.00813.2009
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Temporal Modulation Tradeoff in the Inferior Colliculus

Abstract: Rodríguez FA, Read HL, Escabí MA. Spectral and temporal modulation tradeoff in the inferior colliculus. J Neurophysiol 103: 887-903, 2010. First published December 16, 2009 doi:10.1152/jn.00813.2009. The cochlea encodes sounds through frequency-selective channels that exhibit low-pass modulation sensitivity. Unlike the cochlea, neurons in the auditory midbrain are tuned for spectral and temporal modulations found in natural sounds, yet the role of this transformation is not known. We report a distinct tradeof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
111
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(127 citation statements)
references
References 67 publications
13
111
3
Order By: Relevance
“…In our view, some recent neurophysiological findings appear to provide consensual validation of our behavioral and theoretical results (Rodr ıguez et al, 2010;Middlebrooks and Snyder, 2010). Both sets of investigators measured responses of neural units within the inferior colliculus (IC) of cats.…”
Section: Discussionsupporting
confidence: 68%
“…In our view, some recent neurophysiological findings appear to provide consensual validation of our behavioral and theoretical results (Rodr ıguez et al, 2010;Middlebrooks and Snyder, 2010). Both sets of investigators measured responses of neural units within the inferior colliculus (IC) of cats.…”
Section: Discussionsupporting
confidence: 68%
“…Frequency and temporal resolution are inversely related and shift systematically along the dorsoventral and caudal-rostral dimensions of the midbrain (Read et al, 2009;Rodriguez et al, 2010). We have suggested that this inverse relationship is a trade-off in optimal encoding of different features.…”
Section: Discussionmentioning
confidence: 82%
“…In the cat, response resolution for tone and modulated noise changes along the approximate caudal-to-rostral axis of the midbrain inferior colliculus (Read et al, 2009;Rodriguez et al, 2010;Schreiner and Langner, 1988). Changes in frequency organization and bandwidth also have been observed along the caudal-to-rostral axis in cat thalamus (Calford, 1983;Rodrigues-Dagaeff et al, 1989;Rouiller et al, 1989) and the dorsoventral dimension of cat primary auditory cortex (Read et al, 2002;Schreiner et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological investigations in several animal species have reported single neurons tuned to specific spectrotemporal modulations at various stages of the auditory pathway [e.g., inferior colliculus (8), auditory thalamus (9)] and in the primary auditory cortex (10,11). Intracranial electrocorticography (ECoG) recordings (12,13) as well as noninvasive functional neuroimaging studies (14,15) suggest that similar mechanisms are also in place in the human auditory cortex.…”
mentioning
confidence: 99%